Kallistatin levels in HIV-infected patients and effects of statin therapy. (2nd January 2017) - Eckard, Allison Ross; Cho, Soohee; O'Riordan, Mary Ann; McComsey, Grace A.
Abstract: Background: Kallistatin, a serine proteinase inhibitor, has vasodilatory and anti-inflammatory properties and is increased in other inflammatory conditions. We measured kallistatin in HIV for the first time, examined its relationship with inflammation, and determined if statin therapy affected levels. Methods: Kallistatin levels were measured in subjects from a randomized, double-blinded, placebo-controlled trial. Results: One hundred and thirty-five HIV-infected subjects were included. Kallistatin levels were 28.4 μg/mL at baseline and not affected by rosuvastatin. Levels were correlated with high-sensitivity C-reactive protein (hsCRP), interleukin-6, fibrinogen and insulin resistance. Conclusions: Kallistatin levels were correlated with some markers of systemic inflammation and should be further explored in the HIV population.